Implications of Wearable Technology for Improved Patient Monitoring and Self-Management in Nursing Practice - Alanazi, Maryam Salem; Suaid, Waad Khalid; Alharbi, Reem Suwaliem; Majrashy, Shmaaah Ahmed; Alanazi, Reem Ayed; Alanazi, Maha Murdi; Almutairy, Najwa Thawab; Alshaykh, Azzah Idris Bin; Alshammari, Hala Matub; AlOnazi, Bashaier Eid; Alsaleh, Atheer Adel; Almuwalad, Razan Sultan (Journal of Ecohumanism, 2024)
The rapid evolution of wearable technology has introduced significant advancements in healthcare, particularly in the realm of nursing practice, where it is reshaping patient monitoring and self-management strategies. Wearable devices—ranging from fitness trackers and smartwatches to specialized health monitors—enable continuous, real-time tracking of a wide range of physiological metrics such as heart rate, blood pressure, glucose levels, and sleep patterns. These devices provide nurses with a comprehensive understanding of patients’ health outside traditional clinical settings, offering a more proactive, personalized approach to care. This real-time data empowers both healthcare providers and patients, enhancing patient engagement and facilitating early intervention for chronic disease management. Wearables have shown promise in improving health outcomes by promoting patient self-management, reducing hospital readmissions, and preventing complications associated with conditions like diabetes, hypertension, and cardiovascular disease. However, challenges such as ensuring data accuracy, maintaining patient privacy, addressing device usability, and achieving seamless integration into existing healthcare systems remain significant barriers. This article explores the profound implications of wearable technology in nursing practice, focusing on its potential to improve patient outcomes through enhanced monitoring, data-driven care, and patient empowerment. Additionally, the article discusses the ethical, logistical, and technological hurdles that need to be addressed to maximize the benefits of wearables, and outlines the future possibilities for wearable technologies in advancing healthcare delivery and nursing practice.